2011
DOI: 10.1111/j.1365-3156.2011.02753.x
|View full text |Cite
|
Sign up to set email alerts
|

Need for improved antimicrobial and infection control stewardship in Vietnamese intensive care units

Abstract: Summaryobjective Survey of antibiotic consumption, microbial resistance and hygiene precautions in the intensive care units of three hospitals in northern Vietnam.methods Observational study. Data were collected from the microbiological laboratories. Antibiotic consumption was determined based on quantities of drugs delivered from the pharmacy. A protocol to observe the application of hygiene precautions was developed and used. Bacteria were typed and tested for drug susceptibility using the disc-diffusion met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…Several hospitals have poor availability of water, soap and wipes. A recent study in ICUs showed hygiene precautions to be poor with fewer than 50% of patient contacts incorporating appropriate hand hygiene [47]. …”
Section: Resultsmentioning
confidence: 99%
“…Several hospitals have poor availability of water, soap and wipes. A recent study in ICUs showed hygiene precautions to be poor with fewer than 50% of patient contacts incorporating appropriate hand hygiene [47]. …”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of CRE, including CP-CRE, is high in the tertiary hospitals of the larger South Asian countries (10, 53, 62-71, 75, 82, 83, 99, 101, 102) but much lower in similar hospitals in Southeast Asia (74,114,120,121,129,134,142,147,149,150,157,161). As seen by the numerous reports of CP-CRE exportation from South and Southeast Asia (6,174,(176)(177)(178)(179)(180)(181)(182)(183)(184), international dissemination of CP-CRE appears to be a far greater problem than that of CRAB, and it will conceivably be more difficult for other countries to control CP-CRE within their own borders if this is also not tackled at its root in South and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…The few reports highlighting CRE prevalence in Vietnamese institutions are summarized in Table 5. The multicenter ICU study conducted between 2012 and 2013 showed that 15% of K. pneumoniae isolates were resistant to the carbapenems (142), which was much higher than the 3% found in the earlier 2007 ICU study (147). Up to 1.1% of Enterobacteriaceae isolated between 2010 and 2012 were found to be CRE in a surgical hospital in Hanoi (149).…”
Section: Vietnam There Is No National or Regional Antimicrobial Resimentioning
confidence: 94%
See 1 more Smart Citation
“…In a European multi-centre cross-sectional prevalence study of academic ICUs, there were 14% of Klebsiella ESBL-producers, and nearly 25% of Pseudomonas aeruginosa isolates were carbapenemresistant [10] . ICUs in emerging economies report notably higher prevalence of ESBL-producers [11][12][13] and carbapenemresistant organisms [11][12][13][14] . Of note, the majority of multi-resistant Acinetobacter (MRA) isolates in these studies also demonstrates reduced susceptibility towards carbapenems [11][12][13] .…”
Section: Antibiotic Resistance In Icu Its Contributors and Impactmentioning
confidence: 99%